Exercise to support optimal immune function - Baker, F. L.; Simpson, R. J (ACSM's Health & Fitness Journal, 2021)
Exercise immunology is a relatively new discipline that came of age in the late 1980s (1). Early work in the field showed that individuals who engaged in regular exercise of moderate intensity were less likely to report incidences and symptoms associated with upper respiratory tract infections (URTIs) compared with sedentary individuals (2). This work triggered a surge in studies focused on examining how the immune system responds to both acute (single bout) and chronic (training) exercise in different groups, including athletes, older adults, people with obesity, and individuals living with HIV (3). Questions related to intensity and duration, mode (e.g., endurance versus resistance), single versus multiple bouts, and the aspects of immunity that are affected by exercise were quickly investigated and followed up with mechanistic studies in animals (3). From this work, there is now a general consensus that regular bouts of short-lasting (<45 minutes) moderate- to vigorous-intensity exercise are beneficial for host immune defense, particularly in older adults and individuals with chronic diseases (1,2). This intensity and duration of exercise also has been shown to lower the risk of respiratory infection/illness and some cancers. Unaccustomed prolonged arduous exercise that far exceeds the physical activity (PA) levels recommended for health (i.e., those typically practiced by high-performance athletes and the military) is considered by some to have detrimental effects on the immune system. However, this remains a contentious issue (1) and should not be used to discourage the vast majority of the population from engaging in daily exercise.